EFEKTIVITAS BANTUAN LANGSUNG SEMENTARA MASYARAKAT SEBAGAI KOMPENSASI KENAIKAN HARGA BAHAN BAKAR MINYAK TAHUN 2013 BAGI RAKYAT MISKIN - Alliyah, Siti (Potensio, 2013)
Impact of BBM increase to the addition of the poor 4 million people. Thats the goverment setup a compensation as mitigation or prevention. One of the program is the immediatetemporary relief society (BLSM) to give four months after the BBM increase was decided.Object of BLSM is 15,5 target million households (RTS) with compesation is Rp 150,000 permonth. The allocation of funds amounting to Rp 9,7 trillion. The question is whether thegoverment program effective?Keywords: Effectiveness, the immediate temporary relief society, compensation of BBM